Love actually - Universal Pictures (Firm).; Studio Canal; Working Title Films; DNA Films (Universal City, Calif. Universal, 2004)
It's all about love and holiday cheer in London. The Prime Minister is smitten with his caterer; a widower's young son nurses the ultimate schoolboy crush; a writer falls for his Portuguese housekeeper; a devoted wife and mother copes with her potentially unfaithful husband; and a lovelorn American is desperately attracted to a colleague.
Originally released as a motion picture in 2003.
Special features: commentary by director Richard Curtis and actors Hugh Grant, Bill Nighy & Thomas Sangster; deleted scenes with commentary; the music of the film with introductions by the director Richard Curtis; music video.
Director of photography, Michael Coulter ; editor, Nick Moore ; music, Craig Armstrong ; costume designer, Joanna Johnston ; production designer, Jim Clay.
Alan Rickman, Bill Nighy, Colin Firth, Emma Thompson, Hugh Grant, Laura Linney, Liam Neeson, Martine McCutcheon.
MPAA rating: R; for sexuality, nudity and language.
DVD, Region 1; Dolby Digital.
Keywords: Man-woman relationships -- Drama; Romances -- Drama; Christmas -- England -- London -- Drama